2009
DOI: 10.1590/s1519-38292009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de alfa-tocoferol no soro e leite materno de puérperas atendidas em maternidade pública de Natal, Rio Grande do Norte

Abstract: Objectives: to evaluate levels of alpha-tocopherol i n t h e s e r u m a n d b re a s t -m i l k o f w o m e n a t v a r i o u s stages in lactation and to confirm whether nutrition a l l y a p p ro p r i a t e l e v e l s o f v i t a m i n E a re p re s e n t i n the milk given to the babies.Methods: thirty-two child-bearing women with an average age of 25 years took part in the study. 5 mL of blood and 2 mL of colostrum were collected, under fasting conditions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
2
8
1
3
Order By: Relevance
“…The study by Garcia et al, 15 however, found a positive correlation between the biochemical nutritional status in alpha-tocopherol and its concentration in transitional milk (r = 0.456, p = 0.009), demonstrating the importance of adequate maternal nutritional status. A study performed in Russia also demonstrated this correlation.…”
Section: Biochemical Nutritional Status In Alpha-tocopherol and Matermentioning
confidence: 87%
See 2 more Smart Citations
“…The study by Garcia et al, 15 however, found a positive correlation between the biochemical nutritional status in alpha-tocopherol and its concentration in transitional milk (r = 0.456, p = 0.009), demonstrating the importance of adequate maternal nutritional status. A study performed in Russia also demonstrated this correlation.…”
Section: Biochemical Nutritional Status In Alpha-tocopherol and Matermentioning
confidence: 87%
“…However, Garcia et al 15 observed that the concentration of alphatocopherol, considering the infant's need (4 mg/day) 18 and the daily consumption of 780 mL/day of milk, indicates an apparent nutritional inadequacy of transitional milk in their study, conducted in Northeastern Brazil. Considering this fact, it has been observed that other studies also showed this possible insufficient supply, when analyzing the content of alpha-tocopherol in transitional and mature milk.…”
Section: Lactation Stagementioning
confidence: 89%
See 1 more Smart Citation
“…As lactantes têm sido consideradas como grupo biologicamente vulnerável e sob risco de apresentar estado nutricional marginal ou deficiente em vários micronutrientes 8 . O estado nutricional materno constitui um determinante crítico do resultado da gravidez, tanto para a mãe como para o concepto 16 .…”
Section: Discussionunclassified
“…A correlação da concentração plasmática de alfa-tocoferol materno e sua influência na quantidade de vitamina E no leite humano foi comprovada na literatura. Garcia et al 28 encontraram correlação positiva entre concentrações adequadas de alfa-tocoferol sérico e seu aumento no leite de transição (r=0,456; p=0,009), evidenciando a importância de um bom estado nutricional materno em vitamina E na composição do leite humano.…”
Section: Discussionunclassified